2014
DOI: 10.1159/000360941
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Therapy of Chronic Hepatitis B

Abstract: Chronic hepatitis B (CHB) results from the inability of the host's immune system to control viral replication. Interferon-α (IFN-α) therapy can convert CHB into inactive hepatitis B virus (HBV) infection in 20-30% of the treated patients. In spite of the low response rate, IFN-α therapy has the advantage of having a limited duration and being effective even after therapy, as demonstrated by a much higher incidence of HBsAg clearance in responders to IFN-α than in naturally occurring inactive HBsAg carriers. IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The CHB patients in this study were mostly infected with HBV genotype B or C, but response rates did not differ significantly between genotype groups. Using multivariable logistic regression analysis, previous studies found no significant differences among CHB patient genotypes despite trends suggesting that genotype B may have a slightly better response to PEG‐IFN therapy than genotype C . Therefore, single parameters were of limited value for predicting HBeAg seroconversion or HBsAg loss and guiding decisions about initiating PEG‐IFN therapy.…”
Section: Discussionmentioning
confidence: 97%
“…The CHB patients in this study were mostly infected with HBV genotype B or C, but response rates did not differ significantly between genotype groups. Using multivariable logistic regression analysis, previous studies found no significant differences among CHB patient genotypes despite trends suggesting that genotype B may have a slightly better response to PEG‐IFN therapy than genotype C . Therefore, single parameters were of limited value for predicting HBeAg seroconversion or HBsAg loss and guiding decisions about initiating PEG‐IFN therapy.…”
Section: Discussionmentioning
confidence: 97%
“…This study demonstrates that AIM2 is associated with an HBV‐clearing immune response and that during chronic HBV this component of the immune response is likely dampened. Of interest is that type‐1 interferon treatment of HBV‐infected patients can lead to reduced or permanent elimination of HBV replication . However, in most patients treated with IFN‐α, the effect is transient, and patients show exacerbated hepatitis in the end.…”
Section: The Role Of Inflammasomes In Liver Diseasementioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 IFN-α has been used for the treatment of HBV infection for two decades. 45 IFN-α belongs to the IFN-α/β system, which mediates antiviral, antiproliferative, immune, and other cellular effects.…”
Section: Plscr1 Physically Interacts With Hbxmentioning
confidence: 99%